THE MORAL POTENTIAL OF SOCIETY IN UZBEKISTAN AND ITS ROLE IN ENSURING SOCIAL DEVELOPMENT (Scientific journal of the Fergana State University, 2023)
This article explains that spiritual potential is a set of opportunities and tools that can be used to develop forms of social consciousness of society, to raise the worldview and spiritual world of its members, to preserve the centuries-old spiritual heritage and to pass it on to future generations, to ensure spiritual security.